Presidential address: examining criminal justice and criminology through the lens of intersectionality - Warren-Gordon, Kiesha (Journal of crime and justice, 2020)
Within the mainstream discipline of criminology there has been a failure to recognize the value of the academic contributions of marginalized individuals in the field. This is manifested in the lack of people of color attending regional meetings which often have very traditional themes and focus. To rectify this situation, I suggest that creating meeting themes that highlight nontraditional theoretical perspectives will provide opportunities for marginalized academics to be highlight there work. My thesis is that creating conference themes that focus on attracting marginalized individuals to regional conferences will move the discipline forward in a robust manner that will embrace more voices that have traditionally been limited.